Inclusive Physical Education Implementation: Case Study in Yogyakarta, Indonesia - Sumaryanti, Sumaryanti; M. Wara Kushartanti, B; Laksmi Ambardini, Rachmah (International Journal of Engineering and Technology, 2018)
In recent years, inclusive education has become a very interesting issue in Indonesian education system. The implementation of this policy has never been evaluated. The study aims to explore an overview of the implementation of inclusive Physical Education (PE) in Yogyakarta, Indonesia. This research used survey with the employment of techniques of observation, interview, and giving questionnaire to 40 PE teachers in inclusive primary schools representing 5 regencies in Yogyakarta. Inclusive PE implementation was observed on the lesson plan documents and learning equipment preparation. All observations, interviews, and questionnaires were analyzed descriptively. The result shows that there is variability across the schools on the implementation of inclusive PE. In general, teachers still have difficulty in managing inclusion learning at primary schools because special infrastructure and facilities for disability are not available yet, and specific instructional models for inclusive schools are limited. Most teachers face difficulty in compiling learning variations to keep children excited, so that inclusive PE implementation in Yogyakarta has not been optimal. Based on the findings, possible recommendation for improvements in implementing inclusive physical education is developing learning model that can also build a character, including empathy, cooperativeness, togetherness, tolerances, and struggle for all students, including disable students.Â Â